Cadmium and lead adsorption in highly weathered tropical soils - Linhares, Lucília Alves; Filho, Fernando Barbosa Egreja; Oliveira, Cristiane Valéria de; Bellis, Vito Modesto de (Pesquisa Agropecuaria Brasileira, 2010)
The aims of this work were to characterize the adsorption of cadmium and lead and to evaluate the influence of soil properties on adsorption parameters of these elements in highly weathered tropical soils. The experiment was performed in four Oxisols and one Ultisol. Soil samples (1 g) were mixed by shaking for 16 hours with 0.01 mol L-1 CaCl2 solutions, to which the following doses were added: 0, 10, 20, 30, 40, 60, and 80 μg mL-1 cadmium, and 0, 10, 20, 40, 60, 80, 100, and 120 μg mL-1 lead in the form of nitrates. The elements in the supernatant were analyzed to determine the adsorbed amounts, and the data were fitted to the isotherms of Langmuir and Freundlich. The experimental results were fitted well to the studied model. Maximum adsorption capacity values were between 136 and 1,604 μg g-1 for cadmium, and between 988 and 1,660 μg g-1 for lead, while binding energies were between 0.0036 and 0.0403 μg mL-1 for cadmium, and between 0.0282 and 1.0425 μg mL-1 for lead. The soil properties correlated to the adsorption of cadmium were pH and cation exchange capacity, and the ones correlated to lead were pH and the levels of iron and aluminum oxides.
Keywords: Ultisol; Oxisol; adsorption isotherm; heavy metals